Aktivitas Antioksidan dan Antibakteri Ekstrak Daun Kersen (Muntingia Calabura L) dengan Metode Microwave Assisted Extraction - Mutammimah, Siti; Supriyanto, Supriyanto; Mu’tamar, Mohammad Fuad Fauzul (Rekayasa, 2022)
Kersen (Mutingia calabura) is a wild plant that is not cultivated and not many people know its benefits. So far kersen plants are only used as a shade even though the plant has the potential as an antioxidant and antibacterial. The purpose of this study is to find out the antioxidant and antibakeri activity of kersen leaf extract. The method used for extraction is Microwave Assited Extraction (MAE) with variations in temperature and extraction time. Analysis of antioxidant activity uses the DPPH method by calculating IC50 values while for analysis of antioxidant anctivity using the bland zone method. The results showed that the temperature and time of extraction affect antioxidant and antibacterial activity. The best treatment is obtained from low temperature treatment and extraction time for 7 minutes with IC50 and bland zone values of 44.21 ppm and 11.05 mm respectively.